Aplikasi Manajemen Perkantoran dan Absensi Online Berbasis Android - Ardiansyah, Aldi; Fitri, Iskandar; Iskandar, Agus (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2021)
This research aims to develop a solution application and make work easier during the Covid-19 pandemic, especially in online attendance activities and office management. This study also completes the shortcomings of previous studies, where previous studies used the geotagging feature. The development tools used by researchers use the android studio and the waterfall System Development Life Cycle (SDLC) development method. The result of this research is an application that is connected to the internet in the process of attendance activities. The attendance data is stored in the database along with the photos entered at the time of attendance.
Keywords: Android; SDLC; Online Attendance; Management